Heterotopic ossification in the submental triangle remote from the vascular pedicle after reconstruction with a fibular free flap: a previously unreported complication. Issue 4 (May 2016) - Panaretou, E.; Blythe, J.N.St.J.; Conti, M.; Brennan, P.A.
Abstract: Fibular free flaps are routinely used to reconstruct segmental mandibular defects after resection. While ossification of the vascular pedicle is uncommon but well reported, to our knowledge, heterotopic ossification remote from the pedicle has not previously been described. We report a case in which this occurred. It serves as a reminder that bony, hard lumps in the neck can present years after reconstruction with a fibular flap.